Hungary : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This Selected Issues paper on Hungary describes the main factors behind the evolution of output in Hungary since 1990, and examines Hungary's future growth prospects with specific focus on the role that structural and macroeconomic policies can play in enhancing those prospects. In this paper, the shortfall in growth relative to the other advanced transition economies is attributed to relatively slow progress with macroeconomic stabilization, stalled structural reform between 1993 and mid-1995, and specific features in the design of Hungary's reform program. The paper also analyzes debt dynamics in Hungary.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet